Efektivitas Model Pembelajaran Project Based Learning (PjBL) Berbantuan Kahoot untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Informatika (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to determine the effectiveness of student learning outcomes in the subject of Informatics at MA Subulul Huda Darma, influenced by the use of the Project Based Learning (PjBL) model assisted by Kahoot. The PjBL approach was applied to create a more active, creative, and enjoyable learning environment. The research method used was a pre-experimental design with a one-group pretest-posttest design. The population in this study consisted of all 11th-grade students at MA Subulul Huda Darma enrolled in the Informatics subject, with a sample size of 30 students. To collect the data, learning outcome tests were administered before (pre-test) and after (post-test) the treatment. The pre-test results showed an average score of 62.83, while the post-test results showed an increased average score of 82.50. Based on data analysis using SPSS version 26 with the paired sample t-test, the significance value (2-tailed) was 0.000 < 0.05, indicating that H₀ is rejected and Hₐ is accepted. Therefore, there is a significant difference between the pre-test and post-test scores. These results indicate that the use of the Project Based Learning model assisted by Kahoot is effective in improving student learning outcomes in the Informatics subject at MA Subulul Huda Darma.